(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2017)
This article aims to provide a brief overview of the work of the Brazilian constitutional courts (better known to us by the term constitutional jurisdiction) in the area of structural litigation. The discussion of structural litigation appears in the courts much more as judicial intervention or control over public policies or public interest litigation. These are more common expressions in our country, but they have a common meaning with what US constitutional doctrine calls structural litigation. It should also be noted that in Brazilian law, although there is a long tradition of expressly providing for class actions3 (incorporating class actions from the US model), structural litigation, or as we have indicated, litigation relating to public policies or matters of public interest, does not, as a rule, take the form of class action litigation. As a result, millions of lawsuits are filed every year, often with similar or even identical legal issues, resulting in an overwhelming number of lawsuits in Brazil, currently close to 100,000,000 (one hundred million lawsuits). This volume of lawsuits causes the inevitable congestion of judicial bodies. As a response to this, various mechanisms have been created in recent years in an attempt to resolve this situation. Firstly, there has been the focus on alternative dispute resolution mechanisms (ADRs, from US law), especially since the publication of Resolution 125/2010 of the National Council of Justice, the body responsible for administrative management and oversight of the Judiciary. In the background, now in 2016, a new Code of Civil Procedure (Law No. 13.105/2015) has come into force, which brings with it the promise of speedy procedural solutions, but, above all, incorporates many procedural mechanisms for the collective resolution of demands, such as the incident for the resolution of repetitive demands (art. 976 et seq.), as well as the mechanism for the resolution of repetitive appeals (art. 1.036). This is the general picture of the subject, in brief. Next, we will discuss the strategic reciprocal relationships between the Judiciary and the structuring of public policies in Brazil, based on the example of public social security policies, which will allow us to examine the role of constitutional jurisdiction (constitutional justice) more broadly in matters of structural litigation and the realization of fundamental rights.